2007
DOI: 10.1021/ja070195b
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Phosphatidylinositol-5-Phosphate Analogues as Ligands for the Nuclear Protein ING2:  Chemistry, Biology, and Molecular Modeling

Abstract: The interaction of PtdIns(5)P with the tumor suppressor protein ING2 has been implicated in the regulation of chromatin modification. To enhance the stability of PtdIns(5)P for studies of the biological role in vivo, two phosphatase-resistant moieties were used to replace the labile 5-phosphate. The total asymmetric synthesis of the 5-methylenephosphonate (MP) and 5-phosphothionate (PT) analogues of PtdIns(5)P is described herein, and the resulting metabolically stabilized lipid analogues were evaluated in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Given the fact that high levels of PtdIns-4,5-P 2 , which is the substrate of type I 4-phosphatase, are widely distributed in both cytoplasm and the nucleus, it is possible that this dephosphorylating process may be the predominate synthetic pathway for PtdIns-5-P. Several PHD fingers containing nuclear proteins are PtdIns-5-P-binding ligands (6,14,15). It has been shown that ING2 is a nuclear receptor for PtdIns-5-P in response to stress, and this interaction and its consequences have been studied extensively (6,8,16). The only known regulator of PtdIns-5-P in apoptotic events identified previously is PIPKII␤ (8).…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that high levels of PtdIns-4,5-P 2 , which is the substrate of type I 4-phosphatase, are widely distributed in both cytoplasm and the nucleus, it is possible that this dephosphorylating process may be the predominate synthetic pathway for PtdIns-5-P. Several PHD fingers containing nuclear proteins are PtdIns-5-P-binding ligands (6,14,15). It has been shown that ING2 is a nuclear receptor for PtdIns-5-P in response to stress, and this interaction and its consequences have been studied extensively (6,8,16). The only known regulator of PtdIns-5-P in apoptotic events identified previously is PIPKII␤ (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological functions of this region are not well understood, it has been reported that PtdIns5P bind to the PHD motif of ING2 [33,111]. Later, it was found that PtdIns3P and PtdIns4P can bind to the PBR [112].…”
Section: The Polybasic Regionmentioning
confidence: 99%
“…Phosphonates are widely distributed compounds in living organisms, performing a variety of functions. Introduction of phosphonate, as bioisosteric group to phosphate, has been used in the development of drugs or searching for new therapeutic substances regarding their stability in the conditions of the enzymatic hydrolysis [5,6]. Moreover, among phosphonates, one can find active substances such as antiviral, antibacterial, antitumor, and drugs used in the treatment of osteoporosis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%